2008
DOI: 10.1016/j.seppur.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication-assisted preparation of water-in-oil emulsions and application to the removal of cationic dyes from water by emulsion liquid membrane

Abstract: a b s t r a c tThe main objective of this work is the utilization of W/O emulsions prepared by low-frequency ultrasonic irradiation (22.5 kHz) for the removal and recovery of cationic dyes from aqueous solution by emulsion liquid membrane containing di(2-ethylhexyl) phosphoric acid (D2EHPA) as carrier. The important parameters governing the extraction behavior of dyes have been investigated. These parameters were contact time of the external phase with W/O emulsions, external phase concentration, feed phase pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Higher emulsification speed yielded smaller size of emulsion liquid droplets which make the emulsion more efficient to extract phenol from the external aqueous phase. According to Djenouhat et al [20] and Gasser et al [22], smaller size of emulsion liquid droplets gave better dispersion in the external phase while providing more interfacial surface area for mass transfer. They also suggested that high emulsification speed gave good dispersion of internal phase in the membrane phase, thus providing better emulsion stability with lower leakage due to the higher coalescence time.…”
Section: Membrane: External Phase Ratiomentioning
confidence: 98%
See 2 more Smart Citations
“…Higher emulsification speed yielded smaller size of emulsion liquid droplets which make the emulsion more efficient to extract phenol from the external aqueous phase. According to Djenouhat et al [20] and Gasser et al [22], smaller size of emulsion liquid droplets gave better dispersion in the external phase while providing more interfacial surface area for mass transfer. They also suggested that high emulsification speed gave good dispersion of internal phase in the membrane phase, thus providing better emulsion stability with lower leakage due to the higher coalescence time.…”
Section: Membrane: External Phase Ratiomentioning
confidence: 98%
“…For emulsion liquid membrane (ELM) preparation, several publications [9,11,14,19,20,22,23] were referred to. Span 80 was used as a surfactant for ELM due to its popularity as an emulsifier for liquid membrane while Cyanex 923 was proposed to be the carrier for extraction of phenol [10,11,24,25].…”
Section: Preparation Of Emulsion Liquid Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The increase of droplets diameter decreases the interfacial contact area between the emulsion and feed phase and thereby decreases the extraction. Additionally, for higher volume ratios, the volume of organic phase is not enough for enclosing all the internal aqueous phase [22][23][24] and the dispersion of the W=O emulsion was more difficult. From these results and in order to obtain a uniform and homogeneous distribution of the internal phase droplets in the membrane space and a good dispersion of the W=O emulsion in external phase, the volume ratio of internal phase to membrane phase of 1=1 was accepted as the best ratio.…”
Section: Membrane Stabilitymentioning
confidence: 99%
“…In addition, the extended emulsifying process led to the rupture of emulsion and this was probably caused by the coalescence of the internal droplets and the high shearing rate. In addition, according to Chiha et al, prolonged exposure to emulsifying resulted in a significant increase of breakage . As a result, emulsifying time of 5 min was found to be sufficient for emulsification to obtain a stable emulsion for extraction of KL.…”
Section: Resultsmentioning
confidence: 91%